The Effectiveness of Orai Application in Teaching Reading Aloud - Cita Mustika Kusumah; Humaira Restu Maulidia (Ma'soem University, 2021)
Students often get nervous when they have to speak up in English in front of people. This situation also happens in reading aloud subjects at one of the private universities in Bandung. Most of the students are not confident to do public speaking in English. It is related to the students’ pronunciation, intonation, pace, and filler. In line with technological development, the Orai application can be an alternative way of teaching reading aloud. This research focuses on how the Orai application can help the students to be able to speak in English confidently and loudly in the class. This research employed a quantitative design by using classroom action research (CAR). The data collections of the research were pre-test, post-test, and questionnaire. The result of the study shows that the Orai application improved student performances in reading aloud subjects.